Pool boiling heat transfer of HFE-7100 on metal foams - Manetti, Leonardo Lachi [UNESP] (2019)
The search for new techniques to increase boiling heat transfer has been driven by more efficient and compact heat exchangers, especially in microelectronics and equipment with high thermal loads. Two-phase cooling systems are a promising thermal management technology for high-heat dissipation. In this context, the present study investigated the performance of modified heating surfaces consisting of metal foams of nickel (Ni) and copper (Cu). Pool boiling tests were performed using HFE-7100 as working fluid, at saturation conditions. The metal foams surfaces provided a higher heat transfer coefficient compared to plain surfaces and prevented thermal overshoot at the onset nucleate boiling. The Cu foam provided the best performance for the entire boiling curve. In general, for low and moderated heat fluxes, there is a combined effect of surface area and thermal conductivity of foams; the high surface area of Ni foam provides a barrier for the departure of the vapor bubble, inhibiting the cooling effect of the heating surface. For the Cu foam, no significant vapor trapped effect was observed, and the highest heat transfer coefficient was 12.4 kW/m²∙K for a heat flux around 270 kW/m²; in addition, the thermal behavior is a function of the permeability and wickability behaviors of the surfaces.